2010
DOI: 10.1152/ajpregu.00326.2010
|View full text |Cite
|
Sign up to set email alerts
|

High-NaCl intake impairs dynamic autoregulation of renal blood flow in ANG II-infused rats

Abstract: aim of this study was to investigate dynamic autoregulation of renal blood flow (RBF) in ANG II-infused rats and the influence of high-NaCl intake. Sprague-Dawley rats received ANG II (250 ng·kg Ϫ1 ·min Ϫ1 sc) or saline vehicle (sham) for 14 days after which acute renal clearance experiments were performed during thiobutabarbital anesthesia. Rats (n ϭ 8 -10 per group) were either on a normal (NNa; 0.4% NaCl)-or high (HNa; 8% NaCl)-NaCl diet. Separate groups were treated with 4-hydroxy-2,2,6,6-tetramethylpiperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 39 publications
2
30
1
Order By: Relevance
“…By contrast, the cellular mechanisms responsible for the apparently reduced myogenic responses after PE remain to be elucidated. In contrast to the myogenic response noted in the conscious rat (present studies) and in the conscious dog (47), Saeed et al (75) observed a reduced slope of gain reduction and diminished phase peak in anesthetized rats following 2 wk of ANG II at a higher dose (250 ng·kg Ϫ1 ·min…”
Section: Discussioncontrasting
confidence: 95%
“…By contrast, the cellular mechanisms responsible for the apparently reduced myogenic responses after PE remain to be elucidated. In contrast to the myogenic response noted in the conscious rat (present studies) and in the conscious dog (47), Saeed et al (75) observed a reduced slope of gain reduction and diminished phase peak in anesthetized rats following 2 wk of ANG II at a higher dose (250 ng·kg Ϫ1 ·min…”
Section: Discussioncontrasting
confidence: 95%
“…Conversely, in salt-sensitive hypertension ROS-dependent enhancement of AGT may be involved in the development and progression of renal injury (15,26). Saeed et al (37) showed that ANG II-infused rats on a HS diet (ANG II-salt hypertension) developed impairment of dynamic renal blood flow autoregulation, which was attenuated by tempol (37). However, the unique effect of HS on the pathogenesis of ANG II-salt hypertension has not been established.…”
mentioning
confidence: 99%
“…C7+C8, 80-120 minutes after start of drug administration) were subjected to power spectral and transfer function analyses using methods previously described in detail [21]. Data over the range of frequencies for the myogenic response (0.08-0.18) and the tubuloglomerular feedback (TGF) mechanism (0.03-0.06) were analysed [21,30,31].…”
Section: Transfer Function Analysismentioning
confidence: 99%
“…C7+C8, 80-120 minutes after start of drug administration) were subjected to power spectral and transfer function analyses using methods previously described in detail [21]. Data over the range of frequencies for the myogenic response (0.08-0.18) and the tubuloglomerular feedback (TGF) mechanism (0.03-0.06) were analysed [21,30,31]. The slope of gain decrease in the frequency range of the myogenic response was determined by least squares fitting of the linear regression of gain decrease and the phase peak was estimated as the average phase value within the same frequency interval.…”
Section: Transfer Function Analysismentioning
confidence: 99%
See 1 more Smart Citation